PENGARUH METODE VTS (VISUAL THINKING STRATEGY) TERHADAP KEMAMPUAN MENULIS TEKS PROSEDUR SISWA KELAS X SMK SWASTA MARKUS 2 MEDAN (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of the Visual Thinking Strategy (VTS) learning method on the ability of tenth-grade students at SMK Swasta Markus 2 Medan to write procedural texts. The research employs a quantitative approach. The population consists of all tenth-grade students at SMK Swasta Markus 2 Medan. The sampling technique used is cluster random sampling (random selection based on class groups), in which two classes are randomly selected from three tenth-grade classes consisting of 60 students, resulting in a sample of 40 students. The instrument used in this study is a subjective test in the form of an essay. After applying different treatments, the results show that the mean score of the pretest is 61.25 with a standard deviation of 8.66, while the mean score of the posttest is 78.5 with a standard deviation of 33.70. The prerequisite test results indicate that the data are normally distributed and homogeneous. Furthermore, a one-tailed t-test (α = 0.05) is conducted. Based on the results of the t-test, it can be concluded that there is a significant effect of the Visual Thinking Strategy (VTS) learning method on students' ability to write procedural texts in the tenth grade at SMK Swasta Markus 2 Medan, with the final results categorized as good. Keywords: Visual Thinking Strategy (VTS) method, writing ability, procedural texts